PROBLEMATIKA KURIKULUM SEKOLAH DASAR DI ERA DIGITAL: TELAAH KRITIS TERHADAP TANTANGAN STRUKTURAL DAN PEDAGOGIS - Mujiburrahman, Mujiburrahman; Parhanuddin, Lalu; Sarlita Kartiani, Baiq; Najamuddin, M (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The advancement of digital technology has brought about significant transformations in the education system, including at the primary school level. However, the adoption of curricula in response to the digital era continues to face various complex structural and pedagogical challenges. This article aims to critically examine the main challenges faced by primary school curricula in the digital age, focusing on five key issues: the digital access gap, limited digital competence among teachers, curriculum inflexibility, psychosocial impacts on students, and the limitations of digital evaluation systems. This study employs a qualitative method with a systematic literature review approach, drawing upon Scopus-indexed articles relevant to the topic. The findings reveal that disparities in digital infrastructure, weak digital literacy among educators, and rigid curriculum structures are major obstacles to primary education transformation. Moreover, psychosocial impacts such as decreased learning motivation, social isolation, and emotional pressure emerge as serious issues that remain unaddressed in curriculum policy. The lack of inclusive and authentic assessment systems further exacerbates the misalignment between digital learning approaches and the assessments used. As a contribution, this article proposes policy recommendations that include curriculum reform based on flexibility and contextual relevance, strengthening teacher competencies in digital pedagogy, and developing holistic evaluation systems that prioritize student needs. Therefore, primary school curricula in the digital era should be designed not only to enhance technological access and efficiency but also to ensure equity, psychological well-being, and meaningful learning quality.